2018
DOI: 10.1103/physreva.97.032337
|View full text |Cite
|
Sign up to set email alerts
|

Prefixed-threshold real-time selection method in free-space quantum key distribution

Abstract: Measurement-Device-Independent (MDI) QKD eliminates detector side channels in QKD and allows an untrusted relay between two users. A desirable yet highly challenging application is to implement MDI-QKD through free-space channels. One of the major factors that affect the secure key rate in free-space MDI-QKD is atmospheric turbulence. In this work we show two important results: First, the independent fluctuations of transmittances in the two channels can significantly reduce MDI-QKD performance due to turbulen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…It has been shown that a post-selection of the time-intervals with greater transmittance can help to increase the secret key rates [48][49][50]: in this context, the ability of our approach to simulate not only the expected value of the transmittance, but its probability distribution too, may prove to be of great interest. In [51] the authors showed that the detrimental effects of asymmetric and fluctuating losses in measurement-device-independent QKD with decoy states can be counteracted by means of additional losses introduced by the central node.…”
Section: Satellite-based Links: Model and Resultsmentioning
confidence: 99%
“…It has been shown that a post-selection of the time-intervals with greater transmittance can help to increase the secret key rates [48][49][50]: in this context, the ability of our approach to simulate not only the expected value of the transmittance, but its probability distribution too, may prove to be of great interest. In [51] the authors showed that the detrimental effects of asymmetric and fluctuating losses in measurement-device-independent QKD with decoy states can be counteracted by means of additional losses introduced by the central node.…”
Section: Satellite-based Links: Model and Resultsmentioning
confidence: 99%
“…[7] the successful implementation of this protocol was shown for the 144-km atmospheric channel between two Canary Islands. The theoretical analysis of the performance of the decoy-state protocol that utilizes atmospheric quantum channels is given in [15,31,77] and the experimental realization is demonstrated in [25]. The transmitter Alice encodes the pulses in a signal and two decoy states and sends them to the receiver Bob.…”
Section: Decoy-state Quantum Communication Through Turbulent Optical ...mentioning
confidence: 99%
“…On the contrary, the approach used here is a constructive method that allows to determine the PDT starting from the characteristics of the beam and the atmospheric conditions. It has been shown that a post-selection of the time-intervals with greater transmittance can help to increase the secret key rates [47,48,49]: in this context, the ability of our approach to simulate not only the expected value of the transmittance, but its probability distribution too, may prove to be of great interest. Finally, we effectively take into account the contribution due to scattering particles, like fog or haze, making possible to model the effect of different weather conditions, a problem usually not addressed in previous works.…”
Section: Satellite-based Links: Model and Resultsmentioning
confidence: 99%